Performance simulation of a new location searching scheme for mobile communications - ZHANG Xiao-yan1; DU Xiao-feng2; ZHU Xiang-hua2 (Tongxin xuebao)
The proliferation of mobile users and the development of mobile communication services had spurred higher request for location management.So it was highly desired to design an effective location management scheme in the structure of mobile communication.Four old location searching schemes for PCS were reviewed and a new scheme was proposed.Simulation results show that the proposed scheme performs better than the old four ones.